A cross-sectional study of surgical glove perforation during the posterior lumbar interbody spinal fusion surgery: Its frequency, location, and risk factors. Issue 22 (June 2018) - Kang, Min Seok; Lee, Yeong Ryung; Hwang, Jin Ho; Jeong, Eun Taek; Son, In Seok; Lee, Suk Ha; Kim, Tae Hoon
Abstract : Abstract: Lumbar fusion surgery was known to pose a greater risk of surgical glove perforation. However, there has been no study on the glove perforation that can transmit the blood-borne disease to the patient and surgical staff members in the posterior lumbar interbody fusion surgery (PLIFs). We performed a cross-sectional study to investigate the glove perforation during the PLIFs. The study included 37 consecutive patients (10 males and 27 females). All used gloves of surgical staff members, which included the surgeon, assistant surgeons, bone trimmer (who performed local bone trimming and interbody cage preparation), and scrub nurse were collected and were performed to the pinhole water infusion test. The characteristics (i.e., frequency and location of perforated glove) and relative risk of glove perforation were investigated for each participant. The independent risk factors influencing glove perforation were analyzed by multiple logistic regression analysis. The overall operative perforation rate which is a percentage of detected more than one glove perforated event in all cases was 51.4%. The overall glove perforation rate which is the percentage of perforated gloves in all gloves used for surgery was 3.8%. The relative risk of glove perforation by each participant was 2.38 in the surgeon ( P = .002), 1.36 in the bone trimmer ( P = .04), 1.36 in the scrub nurse ( P = .04), and 1.19 in assistant surgeons ( P = .13). And, the volume of trimmed local bone was analyzed as an independent risk factor for glove perforation (ORs = 1.310, P = .02). The overall operative perforation rate in PLIFs is higher than 50%. The surgeon, scrub nurse and bone trimmer were observed as a significant risk factor for glove perforation. And, the volume of trimmed local bone was analyzed as independent risk factor. Since the preparation of the interbody cage is essential for successful lumbar fusion surgery, the bone trimmer must pay attention to the glove perforation during this procedure.